Constraining Alteration Processes Along the Siccar Point Group Unconformity, Gale Crater, Mars: Results From the Sample Analysis at Mars Instrument. Issue 11 (24th November 2022) - Sutter, B.; McAdam, A. C.; Wong, G. M.; Clark, J. V.; Archer, P. D.; Franz, H. B.; Gasda, P. J.; Ming, D. W.; Yen, A.; Lewis, J. M. T.; Schwenzer, S. P.; Turner, S. M. R.; et al.
Abstract: Results from the Sample Analysis at Mars‐evolved gas analyzer on board the Mars Science Laboratory Curiosity rover constrained the alteration history and habitability potential of rocks sampled across the Siccar Point unconformity in Gale crater. The Glasgow member (Gm) mudstone just below the unconformity had evidence of acid sulfate or Si‐poor brine alteration of Fe‐smectite to Fe amorphous phases, leaching loss of Fe‐Mg‐sulfate and exchange of unfractionated sulfur 34 S (δ 34 S = 2‰ ± 7‰) with enriched 34 S (20‰ ± 5‰, Vienna Cañon Diablo Troilite). Carbon abundances did not significantly change (322–661 μgC/g) consistent with carbon stabilization by amorphous Al‐ and Fe‐hydroxide phases. The Gm mudstone had no detectable oxychlorine and extremely low nitrate. Nitrate (0.06 wt.% NO3 ), oxychlorine (0.13 wt.% ClO4 ), high C (1, 472 μg C/g), and low Fe/Mg‐sulfate concentration (0.24 wt.% SO3 ) depleted in 34 S (δ 34 S = −27‰ ± 7), were detected in the Stimson formation (Sf) eolian sandstone above the unconformity. Redox disequilibrium through the detections of iron sulfide and sulfate supported limited aqueous processes in the Sf sandstone. Si‐poor brines or acidic fluids altered the Gm mudstone just below the unconformity but did not alter underlying Gm mudstones further from the contact. Chemical differences between the Sf and Gm rocks suggested that fluid interaction was minimal between the Sf and Gm rocks. These results suggested that the Gm rocks were altered by subsurface fluids after the Sf placement. Aqueous processes along the unconformity could have provided habitable conditions and in some cases, C and N levels could have supported heterotrophic microbial populations. Plain Language Summary: The Curiosity Rover investigated the chemistry and mineralogy of rocks in the Glen Torridon region of Gale crater, Mars. Rocks sampled across an unconformity (representative of a time gap between when two sedimentary rocks were deposited) gave insight into how they were altered over time. The Glasgow mudstones, below the unconformity, were formed in a lake environment while the younger Stimson sandstones above the unconformity were formed from ancient sand dunes. Using the Sample Analysis at Mars Evolved Gas Analysis (SAM‐EGA) experiment, solid powdered samples from these rocks were heated and released gases (e.g., water, carbon dioxide, and sulfur dioxide) were tracked. These gases revealed a complex history of alteration through the rocks. The Glasgow mudstones were characterized by acidic or Si‐poor brine alteration, variable sulfur, low amounts of carbon, and no nitrate or oxychlorine. SAM‐EGA results from the Stimson sandstone showed rocks that were less altered, had higher levels of carbon, different sulfur compounds and sources, and some nitrate/oxychlorine. Together, these results suggested that the Glasgow rocks were altered by subsurface fluids after Stimson sandstone placement. Aqueous processes along the unconformity could have provided habitable conditions and in some cases, C and N levels could have supported heterotrophic microbial populations. Key Points: Subsurface silica‐poor brines or acidic fluids altered mudstones just below the Siccar Point group unconformity Stimson formation sandstone above the unconformity was exposed to limited aqueous alteration Aqueous alteration processes along the unconformity could have provided habitable conditions and in some cases, sufficient microbial C and N